Active Labor Market Programs : How, Why, When, and To What Extent are they Effective? - Brown, Alessio J.G. (World Bank, Washington, DC, 2014)
Active labor market programs (ALMPs) aim to keep workers employed, bring them into employment, increase their productivity and earnings, and improve the functioning of labor markets. ALMPs to retain employment, for example, work-sharing schemes, should be used only for short periods during severe recessions. More cost-effective and useful during recoveries are ALMPs to create employment, which strengthen outsiders labor market attachment and support the outflow out of unemployment. Training programs are especially effective over the long term, particularly the more they target disadvantaged outsiders. ALMPs that improve labor market matching are highly beneficial, but effective only in the short run. ALMPs in general might be more cost effective over the long term (3-10 years) and some may even be self-financing, suggesting that long-term evaluations are needed to better ascertain the impact of individual policies.